What Are They Looking for? Exploring the Motivation of Sales Staff in Beijing - Ding, Xiaoyi (2011)
Among business practitioners, it is a conventional wisdom that motivating sales staff is essential for any organisation aspiring to succeed. However, the process of motivating is complicated because of the diversity of individual’s needs. Besides, differences in culture may lead to different job attribute preferences across countries. Based on the content theories on motivation, this paper explores the non-financial motivational factors on sales staff in China. This study also illustrates how Chinese cultural heritages, specifically Confucius ideology have affected the needs and the job attribute preferences of sales staff in modern Chinese societies. In addition, the dissertation provides information on the relationships between leadership styles and work motivation among the Chinese sales staff.